35 + 6 ( x - 2 ) = 3 + x Me ajudem
Soluções para a tarefa
Respondido por
1
equação do 1° grau, vamos lá!!!
35 + 6 ( x - 2 ) = 3 + x
35 + 6x - 12 = 3 + x
23 -3 = x- 6x
20 = -5x
x= -20/5
x = -4
35 + 6 ( x - 2 ) = 3 + x
35 + 6x - 12 = 3 + x
23 -3 = x- 6x
20 = -5x
x= -20/5
x = -4
Respondido por
0
35 + 6 ( x - 2 ) = 3 + x
35 + 6x -12 = 3 + x
35 - 3 -12 = x -6x
20 = - 5x
20/-5 = x
-4 = x
bons estudos!
35 + 6x -12 = 3 + x
35 - 3 -12 = x -6x
20 = - 5x
20/-5 = x
-4 = x
bons estudos!
Perguntas interessantes
Matemática,
1 ano atrás
Física,
1 ano atrás
Geografia,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás